UJI KESUKAAN WINGKO BABAT BERBAHAN TEPUNG KEDELAI - Setyo Widiarto (LPPM and Travel Operation Department Universitas Asa Indonesia, 2025)
Wingko babat is one of the culinary snacks originating from the Babat area, Lamongan, East Java, which is made from white glutinous rice flour, grated coconut, granulated sugar, coconut milk, and water, it has a sweet and savory taste. Many studies have produced wingko babat products with substitute ingredients, one of which is adding soy flour in this study. This study aimed to provide food alternatives for those on a low-carb diet, determine the effect of soy flour on the characteristics and shelf life of wingko babat, and determine the level of respondent preference for modified wingko babat products with soy flour substitution. The method used in this study is the experimental method. The experimental method is carried out to determine how a treatment is compared with various variables. The study used a questionnaire to determine the respondents' preference for wingko babat products substituted with soy flour in terms of taste, color, texture, and aroma. In this study, the author conducted experiments with three different concentrations: soy flour concentrations of 10%, 20%, and 30%. Analysis of the results of the preference test showed that wingko babat with a 10% substitution of soy flour was more preferred by respondents in terms of taste, color, and texture, while in terms of aroma, wingko babat preferred by respondents was a 30% substitution of soy flour preferred by respondents.